Persistence of resinous cement residues in dentin treated with different chemical removal protocols - Kuga, Milton Carlos [UNESP]; Reis So, Marcus Vinicius; De Faria-Junior, Norberto Batista [UNESP]; Keine, Katia Cristina [UNESP]; Faria, Gisele [UNESP]; Fabricio, Semiramis; Matsumoto, Mariza Akemi (Wiley-Blackwell, 2012)
The aim of this study was to evaluate the persistence of resin cement residues after dentin surface cleaning with different alcohol-based solutions or an essential oil (eucalyptol). Forty bovine teeth were sectioned in order to expose pulp chamber dentin to be washed with 1.0 mL of 2.5% sodium hypochlorite (NaOCl), followed by 0.1 mL of 17% EDTA application for 3 min, and final irrigation with 2.5% NaOCl. The specimens were air dried and resin-based cement was rubbed onto the dentine surface with a microbrush applicator. After 15 min, the surface was scrubbed with a cotton pellet and moistened with different dentin cleaning solutions, compounding the following groups: G195% ethanol, G270% ethanol, G370% isopropyl alcohol, or G4eucalyptol. The dentin was scrubbed until the cement residues could not be visually detected. Sections were then processed for SEM and evaluated at x 500 magnification. Scores were attributed to each image according to the area covered by residual sealer, and data were subjected to KruskalWallis at 5% significance. Eucalyptol promoted the most adequate dentin cleaning, although no statistical difference was detected amongst the groups (P > 0.05), except between the eucalyptol and 70% ethanol groups (P < 0.05). All the evaluated dentin cleaning solutions were unable to completely remove the cement residues from the dentin surface. Microsc. Res. Tech., 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: endodontics; calcium hydroxide; scanning electron microscopy; smear layer